2019
DOI: 10.1159/000499302
|View full text |Cite
|
Sign up to set email alerts
|

Hyperviscous Semen Causes Poor Sperm Quality and Male Infertility through Induction of Oxidative Stress

Abstract: Background/Aims: Semen hyperviscosity (SHV) is one of the significant factors involved in poor semen quality and male infertility. It also leads major problems during assisted reproduction techniques and in vitro fertilization process. Although influence of SHV on sperm quality, fertilization rate and male infertility have been widely considered, molecular and cellular mechanisms for these abnormalities are not well understood. In this review, we aimed to discuss the proposed cellular and molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…It has been reported that seminal fluid hyperviscosity, which is characterized by a thick and coagulated appearance, occurs in 12-29% of ejaculates [12]. A retrospective study conducted by Elia et al [13] reported that hyperviscosity occurs in 26.2% of male partners of infertile couples [13].…”
Section: Seminal Fluid Hyperviscosity and Infertilitymentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that seminal fluid hyperviscosity, which is characterized by a thick and coagulated appearance, occurs in 12-29% of ejaculates [12]. A retrospective study conducted by Elia et al [13] reported that hyperviscosity occurs in 26.2% of male partners of infertile couples [13].…”
Section: Seminal Fluid Hyperviscosity and Infertilitymentioning
confidence: 99%
“…Leukocytes can also have an important role in the development of hyperviscosity [12]. Patients with higher seminal fluid viscosity have increased concentrations of leukocytes compared to patients with normal viscous semen.…”
Section: Seminal Fluid Hyperviscosity and Male Accessory Gland Infectmentioning
confidence: 99%
See 2 more Smart Citations
“…The ejaculate may also appear in red-brown nuances due to the presence of erythrocytes (haematospermia), while a yellowish colour could be due to liver diseases or consumption of certain vitamins/drugs. (Harchegani, Rahmani, Tahmasbpour, & Shahriary, 2019). Furthermore, infection and inflammation of accessory glands are also associated with semen hyperviscosity (Elia et al, 2009).…”
Section: Appearance and Colourmentioning
confidence: 99%